2014
DOI: 10.1093/europace/euu221
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular lead placement in the latest activated region guided by coronary venous electroanatomic mapping

Abstract: Coronary venous EAM can be used intraprocedurally to guide LV lead placement to the latest activated region free of PNS. This approach especially contributes to optimization of LV lead electrical delay in patients with multiple target veins. Conventional anatomical LV lead placement strategy does not target the vein with maximal electrical delay in many of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Coronary venous electroanatomical mapping allows the assessment of electrical latency exclusively within the CS [23]. A high degree of variability in the location of the site of LEA was observed between patients.…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)mentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary venous electroanatomical mapping allows the assessment of electrical latency exclusively within the CS [23]. A high degree of variability in the location of the site of LEA was observed between patients.…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)mentioning
confidence: 99%
“…Suboptimal LV lead position is a common culprit when evaluating poor outcomes after CRT [47]. Equally, several groups have reported enhanced response rates when targeting tissue which displays evidence of favorable viability [811] or advantageous mechanical [1218] or electrical [1923] properties. This review will evaluate how to define the optimal LV pacing site and the mechanisms by which it is possible to selectively deploy a pacing electrode at this site.…”
Section: Introductionmentioning
confidence: 99%
“…RV lead positions were classified as apical or septal. LV lead positions were classified as basal, mid, or apical in the right anterior oblique view and as anterior, anterolateral, lateral, posterolateral, or posterior in the left anterior oblique view 17. After implantation, atrioventricular and ventriculo-ventricular delays were determined showing the greatest stroke volume (Doppler-guided) or narrowest QRS duration (ECG-based) before discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Coronary venous 3D electroanatomical mapping was performed at the time of CRT implantation as described previously [ 10 ]. In brief, prior to LV lead placement, a 0.014 inch guidewire (Vision Wire, Biotronik SE & Co.KG), which permits unipolar sensing and pacing, was inserted into the coronary sinus and connected to an EnSite NavX system (St Jude Medical, St Paul, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have suggested that CRT may be beneficial in a subset of IVCD patients with evidence of LV activation delay [ 6 9 ]. Recently, we introduced coronary venous electroanatomical mapping as a tool to assess LV electrical activation at the time of CRT implantation in patients with LBBB [ 10 ].…”
Section: Introductionmentioning
confidence: 99%